Determination of D and z values for Salmonella Typhimurium inoculated in an egg-based pastry - Moura-Alves,Márcio (2020)
Abstract Eggs, often used in pastry products, are one of the major transmission vehicles of Salmonella. The main purpose of this study was to evaluate Salmonella Typhimurium thermal resistance, by D and z values determination, in a traditional Portuguese egg-based pastry and its microbial and physical-chemical characterization. Salmonella Typhimurium ATCC 14028 (OXOID C6000L) (Ca. 1.33×108 cfu g-1) was inoculated in a liquid batter consisting of 8 whole eggs, 7 egg yolks, 280 g of wheat flour and 250 g of sugar. D and z values determinations were performed after applying a water bath to vacuum-packed samples of liquid batter (5 g), following thermal treatments: 52 °C (45, 90, 135, 180 and 225 min); 55 °C (15, 30, 45, 60, 70 and 80 min); 58 °C (5, 10, 15, 20, 25 and 30 min) and 61 °C (1, 2, 3, 4 and 5 min). Physico-chemical (aw, pH, moisture, sugar, ashes, protein and free fat) and microbiological determinations (mesophilic microorganisms, psychrotrophic, molds and yeasts, Enterobacteriacea, E. coli; Salmonella spp., Bacillus cereus, Listeria monocytogenes and Staphylococcus aureus) were also conducted in raw liquid batter. It was possible to investigate different combinations of time and temperature for Salmonella Typhimurium inactivation, compared to other studies on egg-based batter, often used to make pastry products. Liquid batter aw before inoculation was 0.94 and pH 7.26. The D values were obtained 53.19 min, 20.45 min, 6.95 min and 1.60 min, at 52 °C, 55 °C, 58 °C e 61 °C, respectively. From the calculated D values, the corresponding z value was 5.96 °C.